2008
DOI: 10.1007/bf03326039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of termite activity on soil environment: A perspective from their soluble chemical components

Abstract: An investigation on varied types of termite mounds relative to the nearby soils that are not inhabited by the termites in different places of Cameroon show that the activity of the termites is increasing the contents of most major and some trace elements in the termite mounds, except for Si and sometimes Fe, Mn, Na and K. These released elements are relocated into newly formed mineral phases that are dissolved by either H 2 O or dilute HCl leachings. The Ca and Mn released by the termite activity testify for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
1
17
0
2
Order By: Relevance
“…The termitarium is highly enriched with humic acids, which serve as terminal electron (e -) acceptors for respiration that supports microbial growth (Lovley et al 1996). Termites are common as "ecosystem engineers" that produce significant physical and chemical modifications to tropical and sub-tropical soils (Semhi et al 2008). They generally go through a sequence of actions, including fetching, and carrying of cementing mineral particles, as well as increase organic matter in the soils used for the construction of their nests, and modify the clay mineral composition of these soil materials (Lopez-Hernandez et al 2006; Roose Amsaleg et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The termitarium is highly enriched with humic acids, which serve as terminal electron (e -) acceptors for respiration that supports microbial growth (Lovley et al 1996). Termites are common as "ecosystem engineers" that produce significant physical and chemical modifications to tropical and sub-tropical soils (Semhi et al 2008). They generally go through a sequence of actions, including fetching, and carrying of cementing mineral particles, as well as increase organic matter in the soils used for the construction of their nests, and modify the clay mineral composition of these soil materials (Lopez-Hernandez et al 2006; Roose Amsaleg et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Termite activity increases mound content of most major, and some trace elements needed for crop production (Table 2) (Semhi et al, 2008). Ca and Mg are released by termite activity and dissolved by water or HCl.…”
Section: Chemical Mechanismsmentioning
confidence: 99%
“…Termites are social insects that build nests in soil or wood (Eggleton et al 2002). The mounds are features built from subsoil taken from a depth as low as 3 metres below the earth surface; thus, the composition of mound soil is closely related to the nature of adjacent subsoil (Semhi et al 2008). Recently, the use of termite mound (TM) to remove Pb(II) (Abdus-Salam and Itiola 2012) and Cr(VI) (Araujo et al 2013), and defluoridation of groundwater (Fufa et al 2013) were reported.…”
Section: Introductionmentioning
confidence: 99%